Financial Management of Indonesian Hajj Against the Yield by Using a Dynamics System Model - Pujiharto, Yaya Ruhenda Casmita; Mariyanti, Tatik; Jayaprawira, Acep R; Terah, Yochebed Anggraini (APTISI Transactions on Management (ATM), 2023)
This research aims to analyze the financial management of Indonesian hajj on yield using a dynamic system model and determine and simulate the return obtained with the expenditure so that the hajj funds remain safe. In addition, the purpose of this research is to provide input on policy strategies to the BPKH in increasing hajj financial yields. The method used in this research is dynamic systems modeling. The resulting model structure formulation is illustrated by a causal loop diagram and a stock-flow diagram. The results obtained were then simulated, and model validation was carried out using AME and AVE. Operational data used in this study uses time-series data. This study's population or several samples are annual historical data during the research period.  In modeling the dynamic system of hajj financial management on yield, it is divided into 2 (two) sub-models, namely the economic sub-model and the social sub-model. Meanwhile, to find out and simulate the yield obtained with the yield expenditure, 3 (three) scenarios were made, namely the existing, moderate, and optimistic scenarios. From the simulation results, it can be seen that making changes to portfolio policies with an optimistic scheme in the form of placements in Islamic Banks with a maximum of 20% and 80% investment and increasing the initial deposits of pilgrims from IDR 25 million to IDR 30 million in 2022 is a government policy intervention that produces optimal yield.